Performance Optimization of Virtual Private Network Based on VXLAN VTEP on MikroTik Devices (Case Study: ID-Networkers West Jakarta) - Narendra Dylan Nugraha; Ari Ramadhan (Sean Institute, 2026)
This study investigates the performance optimization of a Virtual Private Network (VPN) based on Virtual Extensible LAN (VXLAN) utilizing the VXLAN Tunnel Endpoint (VTEP) mechanism on MikroTik RouterOS version 7.19 devices within the ID-Networkers Jakarta Barat environment. The limitations of traditional Point-to-Point Tunneling Protocol (PPTP)-based VPN in terms of stability and scalability motivate the exploration of overlay technology as an alternative solution. The research method employed is network simulation using the PNETLab platform, applying two testing scenarios: PPTP as a baseline condition and VXLAN VTEP as the optimized solution. Performance evaluation is based on Quality of Service (QoS) parameters comprising throughput, latency, jitter, packet loss, and bandwidth, obtained through ICMP packet transmission and testing with iPerf and Wireshark. Results indicate that VXLAN VTEP produces more consistent latency (±5–8 ms compared to ±6–10 ms for PPTP) and 0% packet loss in both scenarios. Furthermore, VXLAN provides significant advantages in network segmentation flexibility and overlay scalability. Although VXLAN throughput is lower due to encapsulation overhead, bandwidth stability is better maintained compared to PPTP. This study concludes that implementing VXLAN VTEP on MikroTik devices is an effective solution for improving inter-site network service quality, particularly in terms of communication consistency and stability.